Characterizing the Complete Mitochondrial Genome of Arma custos and Picromerus lewisi (Hemiptera: Pentatomidae: Asopinae) and Conducting Phylogenetic Analysis. Issue 1 (17th January 2022) - Mu, Yin-Lin; Zhang, Chang-Hua; Zhang, Yu-Jie; Yang, Lin; Chen, Xiang-Sheng
Abstract: We characterized the mitochondrial genome (mitogenome) and conducted phylogenetic analyses of 48 Hemiptera species by sequencing and analyzing the mitogenome of Arma custos (Fabricius) and Picromerus lewisi (Scott). The complete mitogenomes of the two predators were 16, 024 bp and 19, 587 bp in length, respectively, and it contained 37 classical genes, including 13 protein-coding genes (PCGs), 2 ribosomal RNA genes (rRNAs), and 22 transfer RNA genes (tRNAs), and a control region. Most PCGs in these predators use ATN as the start codon. This research revealed that the genes of the two natural enemy species have an A + T content of 75.40% and all tRNAs have a typical cloverleaf structure, with the exception of trnS1, which lacks a dihydrouridine arm. This is the first study to compare the mitochondrial genetic structure of two predatory insects; the mitochondrial genetic structure of individual predatory insects has been sequenced in previous studies. Here, phylogenetic analysis on the basis of amino acid and nucleotide sequences of 13 mitochondrial PCGs using Bayesian inference and maximum likelihood methods were conducted to generate similar tree topologies, which suggested that the two predators with close genetic relationships belong to Asopinae subfamily. Furthermore, the monophyly of the Pentatomoidea superfamily is well accepted despite limited taxon and species sampling. Finally, their complete mitogenome provided data to establish a predator–prey food web, which is the foundation of effective pest management. Our results also enhanced the database of natural enemy insects.